Migraine headache and its association with lifestyle among women. - Mhboubeh Sfavi; Fateme Nazari; Mahmood Mahmoodi (Iran University of Medical Sciences, 2008)
Background and Aim: Migraine is the most common primary headache syndrome with no specific pathologic reason affecting physical, mental and social aspects of quality of life and reduces health-related quality of life (HRQOL). Migraine is the most noticeable medical issue in women's health, since it is more prevalent among them during the reproductive years between the ages of 25 and 55 years. The low frequency of organic causes for and the increasing prevalence of headache suggest individual and environmental factors. The aim of this study is to investigate the associations between migraine headache and lifestyle in women.   Material and Method : This is a case-control study on 170 subjects aged 18-50 years randomly selected by Poisson sampling from population of women with headache referring to neurology clinics of Al-zahra and Nour hospitals affiliated to Isfahan University of Medical Sciences with an absolute diagnosis of migraine by neurologist based on the criteria of the International Headache Society .The control group comprised of all women with no migraine having identical inclusion criteria with the study subjects. The data were collected by interviews with a researcher designed questionnaire. The questionnaire was used after the scientific validity and reliability had been confirmed by content validity and Test-retest, respectively. Descriptive and analytical statistical tests (independent t test, Chi-square test and Fisher exact test) were used to analyze the data.   Results : The findings showed that there was a statistically significant association between some dimensions of lifestyle such as nutrition status and food habits ( P≤ 0.001), sleep and rest pattern (P=0.012), medication habit pattern ( P≤ 0.001) with migraine. Meanwhile, there was no statistically significant association between smoking, physical activity and sport pattern and the level of exposure to life stressors with migraine. The result of the study is in line with some findings of other investigations suggesting that some lifestyle factors probably play a role as migraine precipitating factor. Conclusion: According to the results, for preventing of the attack onset and minimizing side effects of drug abuse, it's necessary to pay more attention to the importance of change and modification of lifestyle in migraine patients and to consider the assessment of lifestyle and health behavior as priorities of health care.